Alteração das reservas de glicogênio em núcleos hipotalâmicos de ratos submetidos à malnutrição protéica durante o período neonatal - Santos, Sebastiao Sergio Lima dos (2000)
Perinatal nutrition has persistent influences on neural development and cognition. In humans and other animals protein malnutrition during the perinatal period causes permanent changes, inducing to adulthood metabolic syndrome. Feeding is mainly modulated by neural and hormonal inputs to the hypothalamus. Hypothalamic glycogen stores are a source of glucose in high energetic demands, as during development of neural circuits. As some hypothalamic circuits are formed during lactation, we attempt to study the effects of malnutrition, during the first 10 days of lactation, on glycogen stores in hypothalamic nuclei involved in the control of energy metabolism. Female pregnant rats were fed ad libitum with a normorprotein diet (22% protein). After delivery each dam was kept with 6 male pups. During the first 10 days of lactation dams from experimental group received a protein free diet and the control group a normoprotein diet. By P10 glycogen stores were very high in the arcuate nucleus and median eminence of control group. Glycogen stores decreased during development. In P20 control animals, glycogen stores were lower when compared to P10 control animals. Animals submitted to malnutrition presented a staining even lower than control ones. After P45 it was difficult to determine differences between control and diet groups because glycogen stores were reduced. We also showed that tanycytes were the cells presenting glycogen stores. Our data reinforce that maternal nutritional state during lactation may be critical for neurodevelopment since it resulted in a low hypothalamic glycogen store, which may be critical for establishment of neuronal circuitry.